Progress Towards Controlled Re-entry and Recovery of CubeSats - Downey, Fergus William (Curtin University, 2023)
The primary objective of this work was to progress towards performing controlled re-entry and recovery missions using CubeSats to increase the frequency of Solar System exploration missions such as extra-terrestrial sample collection and return and planetary Entry, Descent, and Landing. By developing a novel CubeSat platform and further methods to track CubeSats, the cost of developing technologies for these missions has been reduced, meeting the primary objective and enabling more planetary science research opportunities.